Motivasi Berprestasi, Kepuasan Kerja dan Manajerial Kepala Sekolah serta Dampaknya terhadap Kinerja Guru - Rita Sari (Mahesa Research Center, 2018)
Purpose of this research is to know the impact of the independent variable (achieving motivation, job satisfaction, and managerial principal) toward of dependent variable (teachers’s performance). The research was conducted on SD Negeri 7 Idi East Aceh with 30 respondents. The questionnaire was selected as a research instrument. The results of the analysis of the data indicates that (1) partially, independent variables of achieving motivation have a positive impact on teachers’s performance (t = 4.86 > ttable = 2.36); (2) the independent variable (achieving motivation, job satisfaction, and managerial principal of job satisfaction also positively impact on teachers’s performance (t= 3.20 > ttable = 2.36); (3) the principal managerial independent variables take part give a positive impact on performance guru (t = 3.21 > ttable = 2.36); (4) the simultaneous, independent variables does not give a significant impact on teachers’s performance (F = 2.00 < Ftable = 2.92); and (5) were obtained the equations of the regression of Y = 7, 71a + 0, 02X1 + 0, 33X2 + 0, 26X3 it means that when there is an increase in the motivation of overachievers, the satisfaction of teachers, and the principal managerial it will automatically improve the performance of teachers.